Analisa Drainase Sumur Resapan Pada Kampus UNLAM Banjarbaru - Chairil Fachrurazie; Yulian Firmana Arifin; Dewi Sri Susanti (Universitas Lambung Mangkurat, 2002)
One of the enviromental drainage that consider water conservation aspect isdrainage by infiltration rehargr system. Banjarbaru has a high coeffiesient permeability soil and gate on laboratory measurement of soil mechanic, for study area gaied k = 1,23.10 cm/sec dan k = 1,62.10 cm/sec, f = 0,046 m/hr, f = 0,054 m/hr dan f = 0,113 m/hr and ground water level from -7 to -8 meters. According to rainfall intencity measurement, the rainfall intencity is 71,65 m/hr for 5 year return priode with Q = 0,068 A m3/det. Result for infiltration recharge system the dimension is get for H = depth of well, R = radius of well, n = number of wells is drawing in graph.